Cultivar x cropping system interactions in relay and row intercropping of bush beans with different maize plant types - Woolley, Jonathan N.; Rodríguez, W. (Cambridge University Press, 1987)
Bean yield at 2 sites in Costa Rica (Turrialba and Parruas) was affected by the interactions of maize and bush bean cv. with cropping system (relay, row intercropping, and sole cropping). Maize cv. were grouped according to LAI and plant height. In Turrialba, a site with a severe weed problem, leafy maize of intermediate height allowed the highest bean yield in relay cropping but the lowest in intercropping. With tall, leafy maize intercropped beans yielded the same as with short, less leafy cv. In intercrops, tall maize plants shaded the beans less, while in relay crops leafy plants of intermediate height shaded and suppressed weed growth thus benefitting the following bean crop. At the other site, all maize groups had the same effect on beans whether grown in relay or intercropping system. Leafy maize cv. of intermediate height are preferable for sole cropping of maize and, at physiological maturity, for relay cropping with beans when weeds are a problem. Less leafy maize types, however, are better for bean intercropping or for relay crops where the beans are planted before maize maturity. Plant types selected for sole cropping are not necessarily the best for associated cropping systems and one crop may affect another even when their periods of active growth do not overlap. (AS)